Development Of Meat And Vegetable Pate With Functional Properties - K. ISSAYEVA; G. KAZHIBAEVA; A. MUKHAMEJANOVA (International Journal of Pharma and Bio Sciences, 2015)
The article covers aspects of establishment of competitive food products meat and vegetable-based with adjustable, pre-determined characteristics of nutritional and biological value, enriched by the functional ingredients and having a positive effect on different body functions or body in general. The technique employed is similar to that conventionally used in food industry. The composition and properties of the objects is studied by physical-chemical methods according to standards of the Republic of Kazakhstan and International standards. Three options of pate processing are considered, and optimal sample of product for the functional nutrition are developed in the food laboratory of the University. A new functional food product has been designed and tested. It is a pate having a combination of 54 % beef meat and 30 % crushed topinambur. The data obtained provide an exhaustive interpretation of the structure of the pate. Results of research work make it possible to using inexpensive plant raw material in processing food products with functional properties.